Photochemistry of 2-Aminooxazole: A Matrix-isolation and Computational Study of a Putative Key Prebiotic Molecule - Nunes, Cláudio M.; Viegas, Luís P.; Tripathi, Anuj; Braz, Sofia; FAUSTO, RUI (Royal Society of Chemistry, 2025)
2-Aminooxazole 1 is a key intermediate in plausible prebiotic pathways to activated pyrimidine ribonucleotides. However, its photochemistry and underlying reaction mechanism remain unclear. Here, we present a combined matrix-isolation infrared spectroscopic and computational investigation of the UV-induced photochemistry of 1. Narrowband irradiation at 220 nm of 1 isolated in cryogenic Ar or N2 matrices leads mainly to 3-amino-1-formyl nitrile ylide. Minor products included 3-amino-2-formyl-2H-azirine and, most likely, two tautomeric 2-iminooxazoles. The nitrile ylide photoreverts to 1 (380 nm), whereas 2-formyl-2H-azirine photoisomerizes to imidoylketene (320 nm). Spin–flip time-dependent density functional (SF-TDDFT) computations reveal a cascade of conical intersections following excitation to the S2 state of 1, providing a mechanistic explanation for the observed C–O ring-opening and predominant formation of the nitrile ylide. Overall, these findings elucidate the photoreactivity mechanism of 2-aminooxazole and can contribute to understanding the behavior of this pivotal molecule under early Earth UV conditions.
Keywords: Density Functional Theory